Analisis Tekanan Darah pada Penderita Diabetes Melitus di Puskesmas Jungkat, Kalimantan Barat - Nurhayati, Etiek; Yustiana Putri, Naimatul Jannah; Slamet, Slamet (Jurnal Laboratorium Khatulistiwa, 2024)
Diabetes mellitus is a chronic disease, the pancreas does not produce enough insulin, or when the body cannot use insulin effectively. Diabetes mellitus can be followed by various complications, including increased blood pressure or hypertension. Diabetes mellitus is one of the diseases with the 5th highest number of patients at the Jungkat Community Health Center. This study aims to analyze blood pressure in diabetes mellitus patients at the Jungkat Community Health Center, Mempawah Regency, West Kalimantan. This research method is a cross-sectional study. The respondents in this study were diabetes mellitus patients who received treatment at the Jungkat Community Health Center, using an incidental sampling technique.  Research on 40 respondents showed the results: the average systolic blood pressure was 158.03 mmHg, and the average diastolic blood pressure was 87.92 mmHg, while the average blood glucose level was 289.83 mg/dl. The results of statistical analysis using the Chi Square correlation test showed that the p-value (0.001) was smaller than α (0.05). The results of statistical analysis show that there is a relationship between blood pressure and blood glucose levels in diabetes mellitus patients at the Jungkat Community Health Center, Mempawah Regency, West Kalimantan.